2003
DOI: 10.1086/368132
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Zinc, but Not Vitamin A, Improves Seroconversion to Vibriocidal Antibody in Children Given an Oral Cholera Vaccine

Abstract: To investigate whether micronutrient supplementation could improve the vibriocidal antibody response of children to a killed oral cholera vaccine, 2-5-year-old children were randomly assigned to receive vitamin A and zinc (AZ group), vitamin A and a placebo (A group), zinc and a placebo (Z group), or both placebos (P group). All children received 2 doses of the vaccine. The number of children who had a у4-fold increase in vibriocidal antibody was significantly greater in the AZ group than in the P group ( ). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(55 citation statements)
references
References 14 publications
2
51
0
2
Order By: Relevance
“…A potential shortcoming of our study is that our group and others have demonstrated the effect of zinc supplementation (1,3,28), small bowel bacterial overgrowth (20), and antiparasitic drug treatment (8) on immune responses to OCV in young children. We did not assess differences between age groups of such modifiers of immune responses in this study, and these factors deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…A potential shortcoming of our study is that our group and others have demonstrated the effect of zinc supplementation (1,3,28), small bowel bacterial overgrowth (20), and antiparasitic drug treatment (8) on immune responses to OCV in young children. We did not assess differences between age groups of such modifiers of immune responses in this study, and these factors deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…During a trial of CVD 103-HgR in Bangladesh, supplementation with zinc (but not vitamin A) significantly boosted vibriocidal antibody response [118]. Low levels of serum zinc have also been associated with rotavirus risk in Bangladesh [119], though supplementation with zinc did not improve Rotarix immunogenicity during a study in India [120].…”
Section: Malnutrition and Micronutrient Deficienciesmentioning
confidence: 99%
“…It has been estimated that in Bangladesh over 40% of children younger than 5 years of age may have zinc deficiency (131,168). Supplementation with zinc increases the adaptive immune responses to cholera vaccination in children and adults (9,91,131) and in children with shigellosis (140). The effect of micronutrient deficiency on the morbidity and protective immune responses in ETEC diarrhea has not been specifically studied but is an area that needs attention.…”
Section: Etec Infections and Malnutritionmentioning
confidence: 99%